A prothrombotic state and denser clot formation in patients following acute limb ischemia of unknown cause. Issue 187 (March 2020) - Karpińska, Izabela A.; Nowakowski, Tomasz; Wypasek, Ewa; Plens, Krzysztof; Undas, Anetta
Abstract: Introduction: Fibrin clot structure differs between healthy individuals and those following thromboembolic events. Dense and poorly lysable fibrin clots have also been reported in peripheral artery disease. We studied fibrin clot properties and its determinants in individuals with a history of acute lower limb ischemia (ALI) of unknown cause. Materials and methods: In this case-control study, we enrolled 43 patients who experienced ALI of unknown cause, and two age-and sex-matched reference groups: (1) patients with cryptogenic non-lacunar stroke ( n  = 43) and (2) individuals without any history of thromboembolism (n = 43, control group). Plasma fibrin clot properties, along with thrombin generation and fibrinolysis markers were assessed following ≥3 months of anticoagulation. Results: Compared with the control group, the ALI group exhibited more compact plasma fibrin clots (13.4% lower permeability [Ks ], p  = .001), decreased formed clot lysis (12.5% lower D-Drate, p  = .001) and unaltered clot lysis potential, along with enhanced thrombin generation potential (49% higher peak thrombin concentration, p   <  .0001). There were no differences in these variables between ALI and stroke patients. Patients with ALI had slightly higher α2 -antiplasmin and lower plasminogen activator inhibitor 1 levels compared with the stroke and control groups (all p  < .01). Conclusions: Patients who experienced ALI of unknown cause display a prothrombotic fibrin clot phenotype, including increased clot density and hypofibrinolysis associated with higher thrombin generation, which might suggest potential benefits from prolonged anticoagulation in this disease. Highlights: Prothrombotic fibrin clot structure is documented in patients with venous and arterial thromboembolic diseases Compact fibrin clot formation and hypofibrinolysis characterizes patients after acute limb ischemia (ALI) of unknown cause Altered clot properties in patients after ALI of unknown cause are similar to those after cryptogenic non-lacunar stroke Patients following ALI of unknown cause might benefit from prolonged anticoagulant therapy